Functioning and neuronal viability of the anterior cingulate neurons following antipsychotic treatment: MR-spectroscopic imaging in chronic schizophrenia - Braus, Dieter F.; Ende, Gabriele; Weber-Fahr, Wolfgang; Demirakça, Traute; Tost, Heike; Henn, Fritz A. (European neuropsychopharmacology, 2002)
Magnetic resonance spectroscopic imaging provides a non-invasive approach for testing the hypothesis that neuronal function can improve under atypical antipsychotic medication leading to improvement in cognitive function. We studied two groups of schizophrenic patients, one treated exclusively with typical neuroleptics, the other with atypical medications. 1H MR-spectroscopic imaging of the anterior cingulate gyrus was performed in all patients. Perseveration errors in the Wisconsin Card Sorting Test (WCST) served as an additional marker for cingulate gyrus function. Our results showed that N-acetylaspartate (NAA), a measure of neuronal function, was closely correlated with perseveration errors seen on the WCST. Patients treated with atypical medications had fewer errors on the WCST and higher NAA levels than those on typical medications, and there was a correlation between the time treated with atypical medication, higher NAA levels and better test performance. These results suggest that atypical antipsychotics modify the function of anterior cingulate neurons in a specific manner.
Gesehen am 09.11.2020